A Bibliometric Analysis of Pulmonary Alveolar Proteinosis From 2001 to 2021 - Liu, Shixu; Cui, Xiangning; Xia, Kun; Wang, Dandan; Han, Jing; Yao, Xiaoyan; Liu, Xiaohong; Bian, Lingjie; Zhang, Jinzhi; Li, Guangxi (Frontiers in Medicine, 2022)
Background: Pulmonary alveolar proteinosis (PAP) is a rare syndrome that was first described by Rosen et al. in 1958. Despite our considerably evolved understanding of PAP over the past decades, no bibliometric studies have been reported on this field. We aimed to analyze and visualize the research hotspots and current trends of the PAP research field using a bibliometric analysis to help understand the future development of basic and clinical research. Methods: The literature regarding PAP was culled from the Web of Science Core Collection (WoSCC) database. Data were extracted from the relevant articles and visually analyzed using CiteSpace and VOSviewer software. Results: 1,500 qualifying articles were included in the analysis. Publications regarding PAP increased over time. These articles mainly come from 145 institutions of 35 countries. The leading countries were the USA and Japan. Cincinnati Children's Hospital Medical Center (USA) and Niigata University (Japan) featured the highest number of publications among all institutions. Bruce C Trapnell exerts a significant publication impact and has made the most outstanding contributions in the field of PAP. American Journal of Respiratory and Critical Care Medicine was the journal with the highest publications as well as citations, and all the top 5 co-cited journals belong to Q1. Keyword citation bursts revealed that transplantation, tissue-resident macrophage, deficiency, classification, autoimmune pulmonary alveolar proteinosis, sarcoidosis, fetal monocyte, high-resolution ct, and efficacy were the emerging research hotspots. Conclusion: Research on PAP is prosperous. International cooperation is also expected to deepen and strengthen in the future. Our results indicated that the etiology and pathogenesis of PAP, current and emerging therapies, especially the novel pathogenesis-based options will remain research hotspots in the future.